Use of Treated Sewage Wastewater for Irrigation Purpose in Agra Region, Uttar Pradesh : Use of treated sewage water for irrigation - SK Chauhan; MJ Kaledhonkar; RB Singh; RS Chauhan; PK Shishodia (Journal of Soil Salinity and Water Quality, 2023)
Agra district has semi-arid climate and majority of groundwater is saline in nature. Alkali groundwater is also reported in the district. There is scarcity of good quality canal water and groundwater in the region. The treated wastewater from Sewage Treatment Plant (STP), Dhandhupura, Agra, Uttar Pradesh, having capacity of 78 million litre per day (MLD), is being used as important source of irrigation water as well as source of nutrients for crop production by the farmers in the region. The biological oxygen demand (BOD) of untreated sewage ranged from 156 to 225 mg l-1 while it ranged from 47 to 75 mg-1 in case of treated sewage. Under this study different crop fields, irrigated with treated sewage and groundwater, were monitored for crop yields, profits, changes in soil chemical properties, soil organic carbon and available N, P and K for assessing effects of irrigation by treated sewage. There was increase in soil organic carbon as result of use of treated sewage. The fields irrigated by treated sewage showed higher soil organic carbon, higher available N, P and K and higher yields and better profits as compared to fields irrigated by groundwater.